2021
DOI: 10.3390/toxics9030043
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Styrofoam and Microalgae Spirulina platensis in Brackish Water System

Abstract: Styrofoam is a thermoplastic with special characteristics; it is an efficient insulator, is extremely lightweight, absorbs trauma, is bacteria resistant, and is an ideal packaging material, compared to other thermoplastics. The aim of this study was to analyze the interaction between Styrofoam and S. platensis. The study examined the growth of S. platensis under Styrofoam stress, changes in Styrofoam functional groups, and their interactions. The research method was culture carried out in brackish water (12 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
4
0
1
Order By: Relevance
“…It is found that while carbon content increase in a culture, Styrofoam also damage S. Platensis cell. [ 117 ] Polyethylene terephthalate Spirulina sp. 14 days The findings suggest that the presence of Spirulina sp.…”
Section: Waste Management Of Plasticmentioning
confidence: 99%
“…It is found that while carbon content increase in a culture, Styrofoam also damage S. Platensis cell. [ 117 ] Polyethylene terephthalate Spirulina sp. 14 days The findings suggest that the presence of Spirulina sp.…”
Section: Waste Management Of Plasticmentioning
confidence: 99%
“…Table 6 shows the environmental impact of the current packaging material. Styrofoam is made of polyester plastic, which is lightweight and formable (Hadiyanto et al, 2021). Besides, it is also low-cost and highly durable, making it widely used as a packaging material.…”
Section: Figure 5 Electric Cooker Shell Materialsmentioning
confidence: 99%
“…Sampai saat ini styrofoam dijual bebas di toko, warung, bahkan supermarket. Styrofoam banyak digunakan sebagai wadah makanan dan minuman (Hadiyanto et al, 2021). Penelitian ini sependapat dengan penelitian yang menjelaskan terdapatnya kaitan antar pengetahuan penjamah makanan dengan menggunakan styrofoam untuk tempat makanan (Wusqa Abidin, 2016).…”
Section: Hasil Dan Pembahasan Hubungan Pengetahuan Dengan Tindakan Pe...unclassified